EVALUATION OF INFORMATION SECURITY AWARENESS LEVEL OF THE FACULTY MEMBERS - Can GÜLDÜREN (Fırat University, 2020)
The purpose of this study is to develop a web site for faculty members to determine the level of information security awareness and to learn about the effectiveness of the web site which includes developed multimedia materials in gaining information security awareness. A web site including developed multimedia materials has been developed to learn about the effectiveness of the web site in gaining information security awareness. 2x2 mixed design (split-plot) was used in the study. The first factor in the design, which was composed of two levels, consisted of two different experimental processes (Experimental Group which is used web site, Control Group which is not used web site); while the second factor, which was composed of two levels, consisted of pre and post-experiment measurements (pre-test and post-test). The study was carried out twelve weeks with 65 faculty members (Experimental Group:31, Control Group:34) working in a faculty of educational science of a university in Turkey. Faculty members were randomly assigned to one of the two study groups. The data of the study were obtained from the information security awareness scale and the web site evaluation form. The data were analyzed using t-test, ANOVA and ANCOVA. The faculty member' responses to the questions in the interview form were analyzed through frequency and percentage rates. In accordance with the results of the study, when the post-test information security awareness scores of the study groups were compared based on whether using "Information Security and Awareness" web site including multimedia materials or not, it was found that there was a statistically significant difference between the faculty members in Experimental Group and Control Group; and that using "Information Security and Awareness" web site including multimedia materials increased the post- test scores. According to the results of the open-ended questions data analysis, it is considered as useful and well designed in terms of general information about information security awareness. It is also considered as very useful and easy to use web site with video prepared by reference to the detailed and important points.